Deteksi Rasa Kantuk Pengendara Kendaraan Bermotor Menggunakan Image Prosessing: Iwan Setiawan Wibisono,, Marsiska Ariesta - Iwan Wibisono; Marsiska Putri (Multimatrix, 2021)
Abstract - The number of traffic accidents in Indonesia is increasing. One of the main causes of this condition is drowsy drivers. Things like this need to be considered so that the number of accidents due to these factors can be avoided. Therefore, a research was conducted using a digital image processing system to detect driver sleepiness. Digital image processing is intended to determine whether the driver is not sleepy or while driving with input in the form of eye images taken using a digital camera and then entered into the Matlab programming language where the image is taken the value of bw of the sleepy eye area and not a reference image which will be processed with image processing such as cropping, grayscale, iris extraction, thresholding, and analyzed by the bwarea method compared with the image to be identified. The output is information on whether the driver is sleepy or not. Keywords: Bw area, Iris, Digital Image Processing, Thresholding